2012
DOI: 10.1002/jctb.3833
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Fe(II)EDTA‐NO using Paracoccus denitrificans and changes of Fe(II)EDTA in the system

Abstract: BACKGROUND: In the BioDeNOX technology for NOX removal from flue gas, bioreduction of Fe(II)EDTA‐NO and Fe(III)EDTA are core processes. In this study, a newly isolated strain, Paracoccus denitrificans, was used to reduce Fe(II)EDTA‐NO with glucose and Fe(II)EDTA as donor electrons. To better understand the change law of Fe(II)EDTA, the process of Fe(II)EDTA‐NO reduction by P. denitrificans with glucose and Fe(II)EDTA as electron donors was investigated, and the factors that might affect Fe(II)EDTA concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…However, their reductions either take a long time or exhibit unsatisfactory efficiencies. Some researchers therefore proposed to find new strains that could reduce Fe(II)EDTA-NO and Fe(III)EDTA simultaneously (Chen et al,2015;Dong et al, 2012;Dong et al 2014;Li et al, 2013;Liu et al, 2011 andZhang et al, 2007).…”
Section: Evaluation Of a Newly Isolated Klebsiella Sp Dl-1 And Its Imentioning
confidence: 99%
“…However, their reductions either take a long time or exhibit unsatisfactory efficiencies. Some researchers therefore proposed to find new strains that could reduce Fe(II)EDTA-NO and Fe(III)EDTA simultaneously (Chen et al,2015;Dong et al, 2012;Dong et al 2014;Li et al, 2013;Liu et al, 2011 andZhang et al, 2007).…”
Section: Evaluation Of a Newly Isolated Klebsiella Sp Dl-1 And Its Imentioning
confidence: 99%
“…Other studies have shown that N 2 O accumulation was inhibited with a high C/N ratio, sufficient electron donor and a low sulfite concentration [45]. However, N 2 as the final product of Fe(II)EDTA-NO reduction was recognized by most researchers [7][8][9][10][11]13,20,35,37,38,[45][46][47].…”
Section: Analysis Of Reduction Products Of Fe(ii)edta-nomentioning
confidence: 99%
“…The Fe(II)EDTA-NO solution was added into the reactor with the influent through a peristaltic pump. The preparation of Fe(III)EDTA solution referred to the original method where the concentrations were 4-6 mM [20].…”
Section: Influent Qualitymentioning
confidence: 99%
“…Zhang et al 28 and Li et al 29 studied the color change during reducing Fe II EDTA-NO, finding that the color of the Fe II EDTA-NO solution changed from black-brown Fe II EDTA-NO to colorless Fe II EDTA. Zhang et al 28 and Li et al 29 studied the color change during reducing Fe II EDTA-NO, finding that the color of the Fe II EDTA-NO solution changed from black-brown Fe II EDTA-NO to colorless Fe II EDTA.…”
Section: Reaction Mechanism On Reducing Fe II Edta-no Withtdmentioning
confidence: 99%
“…Meanwhile, the Fe II EDTA-NO color change during the reduction process has a significant instruction. Zhang et al 28 and Li et al 29 studied the color change during reducing Fe II EDTA-NO, finding that the color of the Fe II EDTA-NO solution changed from black-brown Fe II EDTA-NO to colorless Fe II EDTA. In this research, it can be observed from Figure 3 that the color was changed from black-brown color into colorless after reduction by TD, and when the NO and N 2 mixture was imported into the colorless solution, the black-brown color was restored.…”
Section: Reaction Mechanism On Reducing Fe II Edta-no Withtdmentioning
confidence: 99%